Core areas of habitat use : the influence of spatial scale of analysis on interpreting summer habitat selection by moose (Alces alces) - Vander Wal, Eric (2004)
I investigated summer habitat selection patterns within the home ranges of 60 GPS-collared adult female moose (Alces alces) in northwestern Ontario. I developed a model that identified the ‘summer’ period for moose and I suggest and test a new approach for objectively delineating areas of intense use, or ‘core’ areas. Once summer and core areas were established, I tested two competing hypotheses to identify differences in habitat selected between the core areas and home range peripheries; (1) core areas represent superior spatial configurations of habitats when compared to home range peripheries; and (2) core areas are selected to contain a subset of ‘preferred’ forage species with higher individual densities or a higher total density of all forage species than home range peripheries. The study was conducted in 2 landscapes characterized by different disturbance patterns created by different timber harvesting systems: modified “guidelines” cut (MGC); and progressive, contiguous clear cut (PCC). Moose move more and faster during the summer than the winter to exploit available forage. I defined moose ‘summer’ as the period during the calendar year when an animal maintains a rate of movement greater than the annual mean. Using a sub-sample (n=32) of animals collared in 2000,1 determined 1 May 2000 as the median date for the ‘winter-summer’ transition (range: 2 April-24 May) and the median transition from ‘summer-winter’ was 25 August 2000 (range: 1 Aug-23 October). Moose home ranges were designated using a 90% adaptive kernel. Within the home range, moose devote a disproportionate amount of time to a fraction of the total area.